Modern level of human capital of the Ukrainian enterprises in the conditions of technological spreads - Dragan, Olena; Tertychna, Liubov; Rybak, Nadiia (My University, 2020)
The modern state of human capital of the Ukrainian enterprises cannot be simply estimated. Without regard to the improvement of some quality descriptions related to the educational level of population, there are some processes in a country, that destroyed it. As depopulation combines with the considerable worsening of population’s health and other its quality descriptions, there were some conditions in Ukraine for transformation of demographic crisis onto demographic catastrophe, that results in instability of community development, negatively influences on economy and social transformations, predetermining the physical, intellectual and spiritual decline of society, results in the lack of skilled human capital in all industries of economy. For the change of situation and progress of human capital trends purposeful efforts of the enterprises, society and state are needed on the basis of scientifically reasonable understanding of problems essence and facilities of their permission. The prospect of further researches in this direction is determination of prospects of human capital development of the enterprises in the conditions of employment patterns change, skills instability caused by technological changes. У статті зазначено, що сучасний стан людського капіталу підприємств України неможна однозначно оцінити. Незважаючи на поліпшення деяких якісних характеристик, пов’язаних з освітнім рівнем населення, в країні відбуваються процеси, що його руйнують. Оскільки депопуляція поєднується із значним погіршенням здоров’я населення та інших його якісних характеристик, в Україні склалися умови для перетворення демографічної кризи на демографічну катастрофу, що призводить до нестабільності суспільного розвитку, негативно впливає на економіку і соціальні перетворення, зумовлюючи фізичний, інтелектуальний і духовний занепад суспільства, призводить до нестачі кваліфікованого людського капіталу в усіх галузях економіки. Для зміни ситуації та тенденцій розвитку людського капіталу необхідні цілеспрямовані зусилля підприємств, суспільства і держави на основі науково обґрунтованого розуміння сутності проблем і засобів їхнього вирішення. Перспективою подальших досліджень у цьому напрямі є визначення перспектив розвитку людського капіталу підприємств в умовах зміни типів занятості, нестійкості навиків, викликаних технологічними змінами.
Keywords: кафедра економіки праці та менеджменту; perspectives; human capital; development; trends; supply indices; перспективи; людський капітал; розвиток; тренди; індекси забезпечення